Strengthening Religious Moderation to Counter the Spread of Transnational Ideologies; a Case Study of Religious Activities in Indonesian Universities - Andy Hadiyanto; Dewi Anggraeni; Ibnu Rusyd; Muhammad Irfan (Tribakti: Jurnal Pemikiran Keislaman, 2026)
The platform of religious moderatism continues to be widely used in the university context as a means to spread wasathiyah religious ideas. This study explores the role of religious institutional activities in fostering religious moderation as a strategic response to the growing influence of transnational Islamic ideologies within Indonesian higher education. Focusing on three prominent public universities Universitas Pendidikan Indonesia (UPI), Universitas Negeri Jakarta (UNJ), and Universitas Negeri Malang (UM). This qualitative research employs a multiple case study approach supported by document analysis, Focus Group Discussion, and observation. The findings reveal that while each institution adopts distinct approaches shaped by their unique socio-cultural and ideological contexts, all three share a commitment to embedding the principles of religious moderation into religious activities. UPI institutionalizes religious programs within the academic structure, UNJ emphasizes inclusivity and diversity, whereas UM integrates values of tolerance and contextual learning. The study affirms that structured mentoring programs rooted in the university’s religious and cultural frameworks are instrumental in shaping students’ moderate religious outlooks. The implications suggest that religious moderation must be mainstreamed into curricular and extracurricular domains through policies that respect institutional contexts.